Experimental study on radial gravity currents flowing in a vegetated channel. (25th February 2022) - Petrolo, D.; Ungarish, M.; Chiapponi, L.; Longo, S.
Abstract: Abstract : We present an experimental study of gravity currents in a cylindrical geometry, in the presence of vegetation. Forty tests were performed with a brine advancing in a fresh water ambient fluid, in lock release, and with a constant and time-varying flow rate. The tank is a circular sector of angle $30^°$ with radius equal to 180 cm. Two different densities of the vegetation were simulated by vertical plastic rods with diameter $D=1.6\ cm$ . We marked the height of the current as a function of radius and time and the position of the front as a function of time. The results indicate a self-similar structure, with lateral profiles that after an initial adjustment collapse to a single curve in scaled variables. The propagation of the front is well described by a power law function of time. The existence of self-similarity on an experimental basis corroborates a simple theoretical model with the following assumptions: (i) the dominant balance is between buoyancy and drag, parameterized by a power law of the current velocity $\sim |u|^{λ-1}u$ ; (ii) the current advances in shallow-water conditions; and (iii) ambient-fluid dynamics is negligible. In order to evaluate the value of ${λ}$ (the only tuning parameter of the theoretical model), we performed two additional series of measurements. We found that $λ$ increased from 1 to 2 while the Reynolds number increased from 100 to approximately $6×10^3$, and the drag coefficient and the transition from $λ=1$ to $λ=2$ are quantitatively affected by D, but the structure of the model is not.